2019
DOI: 10.4028/www.scientific.net/msf.969.86
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Wear Behavior of the ZE41 Mg Alloy

Abstract: High-temperature wear and friction properties of ZE41 alloy were evaluated using a pin on disc tribometer. The microstructure of the alloy has the equiaxed grains of 72±20µm decorated with the rare earth rich precipitates. Result shows that wear rate decreases upto 100°C and then increases until 250°C for all the loading conditions. The wear mechanism study revealed that the underlying thin oxide tribolayer minimizes the wear rate upto 100°C. Above 100°C, thickening of oxide layer due to enhanced oxidation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This kind of morphology suggests the active role of abrasive wear mechanism for both samples. If the wear test temperature is increased to 125°C, the development of a thin oxide tribo-layer on the Mg surface can be seen particularly when the experiments are conducted in open-air [12]. With the increased temperature, the test material becomes soft and may undergo higher material loss.…”
Section: Smaller Grain Size II Reduced Amount Of Intermetallics At Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of morphology suggests the active role of abrasive wear mechanism for both samples. If the wear test temperature is increased to 125°C, the development of a thin oxide tribo-layer on the Mg surface can be seen particularly when the experiments are conducted in open-air [12]. With the increased temperature, the test material becomes soft and may undergo higher material loss.…”
Section: Smaller Grain Size II Reduced Amount Of Intermetallics At Th...mentioning
confidence: 99%
“…Therefore, understanding the wear mechanisms of Mg alloys at high temperature is essential to develop structures that are subjected to relative motion during application. Chiranth et al [12] reported that the wear rate has been increased for ZE41 Mg alloy (grain size of 72 ± 20 µm) due to the excess formation of oxide layer above 100°C. It is true that smaller grain size influences structure-sensitive properties [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Wear studies are becoming critical due to unavoidable sliding contact in certain components. However, limited research is only available on wear and friction behaviour of magnesium alloys like AZ31 [32], AZ61, AZ91 [33][34][35], AM60 [36] and ZE41 [37,38]. The wear and friction behaviour are affected by applied load, sliding velocity, and sliding duration and track diameter [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…In this new era of developing material science, engineering, and related technologies, composite materials have a proven platform of contribution to engineering research. The conventional materials have been replaced in many places due to their drawbacks, and many improvements have been incorporated to increase the desired properties [1,2]. Among these hybrid metal, matrices are currently getting more attention due to their excellent mechanical, tribological, and physical properties in various applications.…”
Section: Introductionmentioning
confidence: 99%